HOMOEOPATHIC MANAGEMENT OF CHRONIC PEDIATRIC IDIOPATHIC THROMBOCYTOPENIC PURPURA: CASE SERIES - Kundu, Dr. Tapas; Kumat, Dr. Omkar; Mirza, Dr. Gulfisha; Kundu, Dr. Rita; Singh, Dr. Trupti (International Journal of Research -GRANTHAALAYAH, 2022)
Idiopathic Thrombocytopenic purpura (ITP) is an autoimmune disorder characterized by decrease in platelets count in blood, leading to manifestations like spontaneous bleeding such as epistaxis, petechiae, ecchymotic patches or painful bruises, gum bleeding or fatal haemorrhages. Here we present three cases of ITP, its manifestation and homoeopathic management. Wong Baker pain rating scale, Adaptive and Maladaptive behavioral scale were used for assessment. A Naranjo criterion for homoeopathy, casual attribution (MONARCH) inventory was used to assess individual curative response of each case, which elucidated the role of homoeopathy in management of ITP. Homeopathic medicine effectively managed the episodes of bleeding and other symptoms in case of chronic pediatric Idiopathic Thrombocytopenic purpura (ITP).